THE ROLE OF MEMORY IN LANGUAGE LEARNING - O‘roqova Ruhshona Shahriyor qizi; Xakimbayeva Ozoda Kalandarovna (TILSHUNOSLIKDA ANTROPOSENTRIZM: YANGI YONDASHUVLAR VA TADQIQOTLAR MAVZUSIDAGI RESPUBLIKA ILMIY-AMALIY ANJUMAN, 2026)
This study explores the central role of memory in the process of language learning, focusing on how different types of memory contribute to vocabulary acquisition, grammar internalization, and communicative competence. Drawing on insights from cognitive and psycholinguistic research, the study examines working memory, long-term memory, and procedural memory as interconnected systems that support language development. The article also discusses practical implications for teaching methodologies, emphasizing strategies that enhance memory retention and retrieval.